3D technologies in dental arcade forensic research - A scoping review - Sundika Ishwarkumar-Govender; Shahed Nalla (Elsevier, 2024)
Scoping reviews in forensic odontology and dental anthropometry provide valuable information. Several current studies indicate different three-dimensional (3D) scanning and digital technologies in clinical dentistry. However, there is a paucity of literature on the utilization and performance of 3D scanner technologies in forensic science and/or medico-legal settings. This study undertook a scoping review of the 3D technologies utilized while researching the applied anatomy of the dentition of modern human forensics. The objectives of this study were to identify which 3D technologies are/were used to determine best practices in usage for research of the dentition of humans and to identify the gaps and challenges faced in the utilization of 3D technologies in dental research covering the forensic domains. Twenty-four key phrases were used in this study to search four databases for the period 1973 to 2023. The initial search yielded 6782 articles, which was then reduced to 1043 after removing any duplicate articles. After title and abstract screening, 35 articles were featured, this was further reduced to 24 articles after applying the selection criteria. The results highlighted the following gaps and challenges faced in the utilization of 3D technologies in dental forensic research: the lack of utilization of 3D equipment for forensic application, as no studies were noted to have been conducted within an African context; a disparity between studies in the Northern and Southern hemispheres, with many studies concentrated in the European and Far East regions and a lack of 3D resources in Africa coupled with the lack of specialized personnel trained to utilize the equipment if available optimally. The scanning modality frequently appears is the 3D Cone Beam Computed Tomography (3D CBCT). Intraoral scans and 3D scanning of dental casts coupled with 3D Geometric Morphometrics were also noted to have been used.